A case of cannibalism in Podarcis siculus campestris De Betta, 1857 (Reptilia, Lacertidae) - Augusto Cattaneo; Mauro Grano (Biodiversity Journal, 2011)
A case-report of cannibalistic behaviour in Italian wall lizard Podarcis siculus campestris De Betta, 1857 isdescribed here along with the first photographic record